2015
DOI: 10.1111/zph.12244
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Characterization of Salmonella Isolated from Feral Pigs Throughout Texas

Abstract: Feral pigs are one of the most abundant free-roaming ungulates in the United States, yet their role in the ecology and transmission of foodborne pathogens is poorly understood. Our objectives were to estimate the prevalence of Salmonella shedding among feral pigs throughout Texas, to identify risk factors for infection, and to characterize the isolates. Faecal samples were collected from feral pigs in Texas from June 2013 through May 2015. Standard bacteriologic culture methods were used to isolate Salmonella … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 29 publications
0
13
0
Order By: Relevance
“…However, in studies conducted in the United States, no significant seasonal variations were observed in samples collected in harvest‐ready feedlots and poorly productive culled beef and dairy cattle (Brichta‐Harhay et al, ; Kunze et al, ). High bacterial shedding during summer is not only reported in domestic animals but also in wild pigs (Cummings et al, ), and corresponds with an increase in Salmonella infections in humans (Cummings et al, ). Hot conditions as observed in summer in temperate areas favour pathogen survival and virulence and are associated with seasonal changes in human behaviour which increase the interactions between pathogens and humans (Ravel et al, ).…”
Section: Salmonella Colonization and Shedding In Ruminants And Suidsmentioning
confidence: 97%
See 1 more Smart Citation
“…However, in studies conducted in the United States, no significant seasonal variations were observed in samples collected in harvest‐ready feedlots and poorly productive culled beef and dairy cattle (Brichta‐Harhay et al, ; Kunze et al, ). High bacterial shedding during summer is not only reported in domestic animals but also in wild pigs (Cummings et al, ), and corresponds with an increase in Salmonella infections in humans (Cummings et al, ). Hot conditions as observed in summer in temperate areas favour pathogen survival and virulence and are associated with seasonal changes in human behaviour which increase the interactions between pathogens and humans (Ravel et al, ).…”
Section: Salmonella Colonization and Shedding In Ruminants And Suidsmentioning
confidence: 97%
“…Salmonella serovars are often isolated in asymptomatic cattle, sheep, pigs, and non‐domestic ruminants and suids (Afema et al, ; Cummings et al, ; Eguale et al, ; Love et al, ; Zishiri, Mkhize, & Mukaratirwa, ). The magnitude and duration of colonization and shedding of Salmonella in animals vary along the different stages of infection or carriage, and not all infected animals shed Salmonella in faeces continuously (Donoghue, Farnell, Cole, & Donoghue, ).…”
Section: Salmonella Colonization and Shedding In Ruminants And Suidsmentioning
confidence: 99%
“…Most infectious and zoonotic diseases usually start as anthroponoses—transmitted from lower vertebrates (primary sources) to humans. Anthroponoses, such as those involving the highly pathogenic avian influenza viruses, Lassa fever virus, Brucella spp., pathogenic Mycobacterium spp., Bacillus anthracis, Escherichia coli O157:H7, Salmonella spp., and rabies virus [5], [6], [7], [8], [9], [10], [11], [12], typically cause serious health hazards among vast animal populations worldwide with the attendant economic and public health consequences being enormous [13]. The majority of these pathogens are on the Centers for Disease Control and Prevention (CDC) bioterrorism agents list [14].…”
Section: Introductionmentioning
confidence: 99%
“…Of 442 feral swine sampled in Texas, 194 animals were found to harbour Salmonella spp. in their faeces and a number of different serovars were detected (Cummings et al., ). These studies were conducted in different regions at different times, further indicating that feral swine are frequently exposed to Salmonella spp.…”
Section: Resultsmentioning
confidence: 99%
“…The diversity of Salmonella spp. isolates detected in wild boar and feral swine suggests these animals are exposed via numerous routes, which may include livestock farming, waste disposal or via consumption of carcasses (Cummings et al., ). Co‐mingling of wild boar with domestic cattle resulted in much higher levels and greater diversity of Salmonella spp.…”
Section: Resultsmentioning
confidence: 99%